Interlaminar Shear, Bending, and Water Retention Behavior of Nano-SiO2 Filler-Incorporated Dharbai/Glass Fiber-Based Hybrid Composites under Cryogenic Environment - L. Natrayan; T. Sathish; S. Baskara Sethupathy; S. Sekar; Pravin P. Patil; G. Velmurugan; Hunde Hailu (Adsorption Science & Technology)
In current history, adding nanoscale and micron-sized filler materials to composite materials for fabrication has been a popular approach for improving the composite’s mechanical characteristics. Due to their lower friction coefficient, excellent mechanical strength modulus, and low moisture uptake, filler-based hybrid composite materials are replacing metallic materials. Glass/Dharbai hybrid composites with nano-SiO2 fillers have been created in this study. After manufacture, the composite materials were treated with liquid nitrogen at 177 K for various durations. Every sample material was cut according to ASTM standards to investigate mechanical features such as ILSS, impact test, and flexural strength. The broken composite specimen was studied using a scanning electron microscope. Water retention studies have been conducted under two distinct liquid solutions: tab or regular water and seawater. ILSS, flexural strength, and water retention were all greater in 4 wt.% of nanofiller-rich composites than in ordinary composites. Compared to 30 minutes, the 15-minute cryo-treated specimens provide the highest mechanical strength. On the other hand, the automobile, aviation, and shipbuilding sectors would benefit from a nanofiller-based composite.